Assembly of heteropoly acid into localized porous structures for in situ preparation of silver and polypyrrole nanoparticles. Issue 64 (30th October 2018) - Liang, Jing; Yu, Lei; Zhang, Jiangyong; Zhao, Shixiong; Zhang, Jiejing; Zhang, Jianfeng
Abstract : An ordered heteropoly acid patterned porous structure is prepared which can be applied to the preparation of silver and polypyrrole nanoparticles. Abstract : A simple and facile method to fabricate porous films which were locally patterned by heteropoly acid was developed in this study. The mixture of poly(methyl methacrylate) and stabilizer dichloromethane solution which contains heteropoly acid aqueous solution, prepared through shaking, was applied to fabricate a reversed microemulsion. After spreading and evaporating the solvent of microemulsion on a glass slide, an ordered honeycomb film was produced by incorporation of heteropoly acid in the cavities. The locally anchored heteropoly acid could be readily applied for the selective modification of the porous films through the in situ chemical reactions in the cavities with the additive agents. The silver nanoparticles were in situ prepared via the reduction of silver ions by reduced state H3 PW12 O40, and the polypyrrole spheres were locally obtained through the oxidative polymerization of pyrrole catalyzed by H3 PMo12 O40 in the cavities. Considering that water-soluble molecules and nanoparticles were universally suitable for the present strategy, the reported approach opened up an efficient way for patterning organically incompatible components on porous polymer films via the assembly of microemulsion droplet carriers to fabricate multi-functional hybrid surface structures.